2023
DOI: 10.1186/s12940-022-00956-7
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide (CO2) emissions and adherence to Mediterranean diet in an adult population: the Mediterranean diet index as a pollution level index

Abstract: Background Research related to sustainable diets is is highly relevant to provide better understanding of the impact of dietary intake on the health and the environment. Aim To assess the association between the adherence to an energy-restricted Mediterranean diet and the amount of CO2 emitted in an older adult population. Design and population Using a cross-sectional design, the association between th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 53 publications
0
7
1
Order By: Relevance
“…On the other hand, the data obtained describe a CF of food consumption twice as high as that reported in Brazil (4489 g CO 2 eq) [ 34 ], France (4170 g CO 2 eq) [ 35 ], and the United States of America (4720 g CO 2 eq) [ 36 ]. These results are different from the conclusion of García, S. et al, which showed that higher MD adherence is related to lower odds of dietary carbon dioxide emissions [ 37 ]. This discrepancy can be explained by the fact that global data were used, and some specific values from the United Kingdom.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, the data obtained describe a CF of food consumption twice as high as that reported in Brazil (4489 g CO 2 eq) [ 34 ], France (4170 g CO 2 eq) [ 35 ], and the United States of America (4720 g CO 2 eq) [ 36 ]. These results are different from the conclusion of García, S. et al, which showed that higher MD adherence is related to lower odds of dietary carbon dioxide emissions [ 37 ]. This discrepancy can be explained by the fact that global data were used, and some specific values from the United Kingdom.…”
Section: Discussioncontrasting
confidence: 99%
“…The environmental pressure of the food system would be attenuated by moving towards a more plant-based (PB) diet [ 37 , 38 ]. Demands of PB products increased over the last several years [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sex, educational level, and age can alter metabolic syndrome severity outcomes [ 11 ]. The second OR adjustment added the MedDiet variable because it was seen inversely related with metabolic syndrome severity [ 10 ] and inversely related to CO 2 emissions [ 53 ]. OR was calculated between each one of the items of the MetS, the MetS severity (low or high) and the quartiles of the amount of CO 2 emitted in kg.…”
Section: Methodsmentioning
confidence: 99%